Davidson's principles and practice of medicine - Ralston, Stuart H.; Penman, Ian D.; Strachan, Mark W.J; Hobson, Richard P. (Churchill Livingstone/Elsevier, 2018)
"This textbook describes the pathophysiology and clinical features of the most frequently encountered conditions in the major specialties of adult medicine and explains how to recognise, investigate, diagnose and manage them. The opening section describes the fundamentals of genetics, immunology, infectious diseases and population health, and discusses the core principles of clinical decision-making and good prescribing. A new second section on emergency and critical care medicine encompasses poisoning, envenomation and environmental medicine, and introduces a new chapter on acute medicine and critical illness. The third section covers the major medical specialties. Two new chapters on maternal and adolescent/transition medicine complement the one on ageing and disease. A new chapter on medical ophthalmology has been included."